Pengaruh Kualitas Dan Partisipasi Tenaga Kerja Perempuan, Serta Faktor Ekonomi Terhadap Kemiskinan Di Indonesia - Fahymah Jamilah; Muhammad Anshari (Media Riset Ekonomi Pembangunan (MedREP), 2026)
Poverty remains a major development challenge in Indonesia despite the declining national poverty rate, with substantial disparities across provinces. These differences indicate that variations in women's human capital, labor market participation, and regional economic conditions may influence poverty in different ways. Previous studies have generally examined women's education, health, labor participation, and macroeconomic factors separately, leaving limited evidence on their combined effects within a single analytical framework. This study investigates the effects of women's average years of schooling, women's life expectancy, the female labor force participation rate, economic growth, and foreign direct investment on poverty across 34 Indonesian provinces during 2018–2025, with the open unemployment rate included as a control variable. Panel data regression was estimated using the Fixed Effect Model with Panel Corrected Standard Errors (FEM-PCSE). The results show that women's average years of schooling significantly reduces poverty, whereas the female labor force participation rate, foreign direct investment, and the open unemployment rate have significant positive effects. Women's life expectancy and economic growth are negatively associated with poverty but are not statistically significant. The model explains 98.6% of the variation in poverty (adjusted R² = 0.9864). These findings emphasize the importance of expanding women's educational attainment, improving the quality of female employment, and promoting more equitable foreign investment to accelerate poverty reduction in Indonesia.